Seasonality and Sleep: A Clinical Study on Euthymic Mood Disorder Patients. (8th December 2011) - Brambilla, Chiara; Gavinelli, Chiara; Delmonte, Dario; Fulgosi, Mara Cigala; Barbini, Barbara; Colombo, Cristina; Smeraldi, Enrico
Abstract : Background . Research on mood disorders has progressively focused on the study of seasons and on the mood in association with them during depressive or manic episodes yet few studies have focused on the seasonal fluctuation that characterizes the patient's clinical course both during an illness episode and during euthymic periods. Methods . 113 euthymic outpatients 46 affected by major recurrent depression and 67 affected by bipolar disorder were recruited. We evaluated the impact of clinical "rhythmical" factors: seasonality, sleep disturbance, and chronotype. Patients completed the SPAQ+ questionnaire, the MEQ questionnaire, and the medical outcomes study (MOS) sleep scale. We used t -test analyses to compare differences of clinical "rhythmical" and sociodemographic variables and of differences in the assessment scales among the diagnostic groups. Results . Patients reporting a family history for mood disorders have higher fluctuations throughout seasons. Sleep disturbance is more problematic in unipolars when compared to bipolars. Conclusions . Sleep, light, and seasonality seem to be three interconnected features that lie at the basis of chronobiology that, when altered, have an important effect both on the psychopathology and on the treatment of mood disorders.